La technologie au service de la démocratie au travail ? Le cas des Whiteboards. - Jean-Sébastien Vayre; Judith Igelsböck (La Nouvelle Revue du Travail)
As part of what economic and political actors call "industry 4.0", multiple digital technologies have modernised most if not all organisation. This can be exemplified by the White Corporation, which has started rolling out whiteboards to ensure an effective deployment of lean management within the organisation, thereby cementing its commitment to becoming a so-called "industry of the future". The lesson here is that despite the aspirations associated with this kind of socio-technical innovation, whiteboards do not promote a more democratic work organisation. The technology may create greater space for autonomy and experimentation with organisational tactics but whiteboards are also conrol instruments aimed at ensuring the implementation of a problematic organisational strategy defined by a very few high-level managers.